Research on Immersion Teaching Method Based on 5G +XR Technology and Reinforcement Learning Model - Xueqing Xie (Advances in Multimedia)
The traditional teaching mode is difficult to meet the needs of modern teaching development because of its single teaching method and insufficient utilization of resources. With the in-depth application of 5G and XR technology in the field of education, the teaching mode based on 5G + XR has become a research hotspot of educational informatization. Therefore, this paper proposed an immersive teaching method based on 5G + XR technology and reinforcement learning model. By analyzing the characteristics and advantages of 5G technology in the field of teaching, this paper expounded that 5G technology not only had an important impact on the reform of modern teaching mode, but also can promote the development of immersive teaching. In addition, based on the analysis of XR teaching theory and its significance, an immersive XR teaching design method based on reinforcement learning model was proposed, and the working principle of immersive XR teaching system and the architecture method of teaching space were given. Finally, the construction scheme of immersive teaching scene based on 5G + XR and the design idea of immersive XR teaching method were put forward. The experiment showed that the immersive XR teaching method proposed in this paper was better than the traditional teaching mode, whether it was the students' learning effect of knowledge or their participation and experience in learning, which also verified that the method proposed in this paper had certain feasibility and superiority. The immersion teaching method based on 5G + XR proposed in this paper can provide a reference for the reform and development of modern education and teaching mode.